Is the Recent Burst of Therapeutic Anti-Tumor Antibodies the Tip of an Iceberg? - Jose A. Garcia-Sanz (Frontiers Research Topics, 2018)
The high effectiveness of antibodies as anti-tumor therapeutic agents has led to a burst of research aiming to increase their therapeutic applications by the use of antibodies against new targets, new antibody formats or new combinations. In this e-book we present relevant research depicting the current efforts in the field.